KNOWLEDGE, CONFIDENCE AND BARRIERS TO IMPLEMENTING IODINE-RESTRICTED DIET IN THYROID CANCER PATIENTS AT 108 MILITARY CENTRAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the knowledge, confidence, and barriers to implementing a low iodine diet of thyroid cancer patients at the 108 Military Central Hospital.Subjects and methods: Cross-sectional study of 250 thyroid cancer patients who were prescribed or had received I131 treatment.Results: Females accounted for 88%; those over 45 years old accounted for 48.8% with a mean age of 45.29 ± 10.96 years. Papillary thyroid cancer accounted for 96%, 98.8% of patients had undergone total thyroidectomy, the metastatic rate accounted for 52.4%. The rate of hormone use accounted for 68.8%; the lowest number of I131 doses was 1 dose, accounting for 51.2%, and ≥ 3 doses accounted for 5.2%. The correct knowledge of thyroid cancer patients about low iodine diet in the question “preparation for radiotherapy is a completely iodine-free diet” accounted for the highest rate of 100%; the lowest correct knowledge rate was in the question “iodine-restricted diet is a low-salt diet” with only 53.2% of patients answering correctly. Thyroid cancer patients were most confident with “can eat iodine-restricted diet if provided with a menu” with 5.84 ± 1.24 points. The lowest barrier was “inconvenient to prepare separate meals from family members” with a score of 2.66 ± 1.49 points.Conclusion: The correct knowledge of thyroid cancer patients about performing low iodine diet accounted for 77.2%; confidence in performing low iodine diet accounted for 52.24 ± 7.98 points and barriers in performing low iodine diet 38.26 ± 10.72 points.
Keywords: Confidence, barriers, iodine-restricted diet, thyroid cancer.